One Size Does Not Fit All: Heterogeneity in Developmental Hematopoiesis - Cristiana Barone; Roberto Orsenigo; Raffaella Meneveri; Silvia Brunelli; Emanuele Azzoni (Cells, 2022)
Our knowledge of the complexity of the developing hematopoietic system has dramatically expanded over the course of the last few decades. We now know that, while hematopoietic stem cells (HSCs) firmly reside at the top of the adult hematopoietic hierarchy, multiple HSC-independent progenitor populations play variegated and fundamental roles during fetal life, which reflect on adult physiology and can lead to disease if subject to perturbations. The importance of obtaining a high-resolution picture of the mechanisms by which the developing embryo establishes a functional hematopoietic system is demonstrated by many recent indications showing that ontogeny is a primary determinant of function of multiple critical cell types. This review will specifically focus on exploring the diversity of hematopoietic stem and progenitor cells unique to embryonic and fetal life. We will initially examine the evidence demonstrating heterogeneity within the hemogenic endothelium, precursor to all definitive hematopoietic cells. Next, we will summarize the dynamics and characteristics of the so-called “hematopoietic waves” taking place during vertebrate development. For each of these waves, we will define the cellular identities of their components, the extent and relevance of their respective contributions as well as potential drivers of heterogeneity.